Penyelenggaraan Angkutan Barang Program Tol Laut Konektifitas - Prasetyawati, Indah (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2024)
As an archipelagic country, in an effort to boost the national economy, equalize the economy and reduce economic inequality between the western and eastern regions, the Government, by carrying the context of Nawa Cita, launched a program entitled: "Connectivity Sea Toll Program". Since 2015 to mid-2024, the sea toll program has resulted in many changes in Indonesia's economic development, especially in reaching the Underdeveloped, Remote, Outermost, and Border areas in Indonesia. This study was conducted in order to provide an overview of the sea toll program in Indonesia to make it easier for readers to understand and identify several important topics regarding the sea toll program in Indonesia. This study also provides information and an overview of the implementation of the sea toll program so far, the impacts of the implementation of the sea toll program, and problems in implementing the sea toll program. The results of the study show that in general the Sea Toll Program has succeeded in distributing logistics from the western to the eastern regions optimally. However, in the context of efficiency, there are obstacles in the form of inefficiencies that occur in return loads in the sea toll program.